PENGARUH KONSELING KELOMPOK TEKNIK TOKEN ECONOMY UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR SISWA KELAS VIII.5 DI MTSN 3 TANAH DATAR - Ferdi; Syahrepah; Masril; Rahmadhani, Fitria (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The problem in this study departs from the low learning discipline of students, which can be seen through behaviors such as being late to class, not doing assignments, lack of focus during learning, and violations of school rules. This condition has an impact on the decline in the quality of the process and learning outcomes. For this reason, effective interventions are needed, one of which is through group counseling with token economy techniques that focus on providing positive reinforcement to form disciplined behavior. This study uses a quantitative method with a one-group pretest-posttest experimental design. The research sample amounted to 10 students of class VIII.5 who were selected using the purposive sampling technique. The research instrument in the form of a learning discipline scale contains 32 items that have been validated. Data analysis was carried out using the t-test and the N-gain test to see the difference in scores before and after treatment. The results of the study showed that there was a significant influence of token economy technique group counseling on improving student learning discipline. The t-test results in a tcal value = 9.649 > ttable = 2.262, so H0 is subtracted and Ha is accepted. The results of the N-gain test showed a moderate improvement category, which means that this technique is effective in modifying more disciplined learning behaviors. It can be concluded that group counseling with token economy techniques has a significant effect on improving student learning discipline. This technique is able to provide systematic reinforcement so that disciplinary behavior can be formed and maintained more consistently.